Effect of TiO2 Loading on Pt-Ru Catalysts During Alcohol Electrooxidation. (10th October 2015) - Hasa, Bjorn; Kalamaras, Evangelos; Papaioannou, Evangelos I.; Vakros, John; Sygellou, Labrini; Katsaounis, Alexandros
Graphical abstract: Highlights: TiO2 can be used to modify Pt-Ru based electrodes for alcohol oxidation. TiO2 modified electrodes with lower amount of metals had higher active surface area than pure Pt-Ru electrodes. TiO2 modified electrodes showed comparable performance with pure Pt-Ru electrode both in a single cell and in a PEM fuel cell under alcohol fuelling. Abstract: In this study, Pt-Ru based electrodes modified by TiO2 were prepared by means of thermal decomposition of chloride and isopropoxide precursors on Ti substrates, characterised by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectroscopy (XPS), electrochemical techniques and CO stripping and used as anodes for alcohol oxidation. The minimization of the metal loading without electrocatalytic activity losses was also explored. TiO2 was chosen due to its chemical stability, low cost and excellent properties as substrate for metal dispersion. It was found that TiO2 loading up to 50% results in a 3-fold increase of the Electrochemically Active Surface (EAS). This conclusion has been confirmed by CO stripping experiments. All samples have been evaluated during the electrochemical oxidation of methanol, ethanol and glycerol. In all cases, the Pt25 -Ru25 -(TiO2 )50 electrode had better electrocatalytic activity than the pure Pt50 -Ru50 anode. The best modified electrode, (Pt25 -Ru25 -(TiO2 )50 ), was also evaluated as anode in a PEM fuel cell under methanol fuelling conditions. The observed higher performance of the TiO2 modified electrodes was attributed to the enhanced Pt-Ru dispersion as well as the formation of smaller Pt and Ru particles.